1 ⋅ 2 1 + 3 ⋅ 4 1 + 5 ⋅ 6 1 + 7 ⋅ 8 1 + …
Let S denote the value of series above. Find the value of e S .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great! Can you find the flaw in the working below?
= > > = 1 1 − 2 1 + 3 1 − 4 1 + 5 1 − 6 1 + … ( 1 1 + 3 1 + 5 1 + 7 1 + … ) − ( 2 1 + 4 1 + 6 1 + … ) ( 1 1 + 3 1 + 5 1 + 7 1 + … ) ( 2 1 + 4 1 + 6 1 + 8 1 + … ) 2 1 ( 1 1 + 2 1 + 3 1 + 4 1 + … ) = ∞
@Calvin Lin The > in the third line is incorrect. Besides, you can't rearrange a conditionally convergent series.
A beautiful use of colors in the answer.
@Calvin Lin Even more Flawful! (1 + 1/3 + 1/5 + .... ) = s1 (1/2 + 1/4 + 1/6 + ....) = s2 s = (1 + 1/3 + 1/5 + .... )- (1/2 + 1/4 + 1/6 + ....) = s1 - s2
s2 = 1/2(1 + 1/2 + 1/3 + .....) = 1/2 ( (1 + 1/3 + 1/5 + ...) + (1/2 + 1/4 + 1/6 + ....) ) = 1/2(s1 + s2) s2 = (s1 + s2 )/ 2 ???? s2 = s1?
S = 1 . 2 1 + 3 . 4 1 + 5 . 6 1 + …
= ( 1 1 − 2 1 ) + ( 3 1 − 4 1 ) + …
E x p a n s i o n f o r l n ( 1 + x ) = x − 2 x 2 + 3 x 3 − … [ F o r ∣ x ∣ < 1 ]
For x → 1 ,
We can a p p r o x i m a t e l y say that
l n ( 1 + x ) = 1 − 2 1 2 + 3 1 3 − … = S
⇒ e S = e ln ( 2 ) = 2
Actually it's convergent for x=1, no "approximately" needed. The behavior on the boundary of the radius of convergence is nontrivial but it turns out that only x=-1 diverges.
Problem Loading...
Note Loading...
Set Loading...
S ⇒ e S = 1 ˙ 2 1 + 3 ˙ 4 1 + 5 ˙ 6 1 + 7 ˙ 8 1 + . . . = 1 1 − 2 1 + 3 1 − 4 1 + 5 1 − 6 1 + 7 1 − 8 1 + . . . = x − 2 1 x 2 + 3 1 x 3 − 4 1 x 4 + 5 1 x 5 − 6 1 x 6 + . . . [ For x = 1 ] = ln ( 1 + x ) = ln ( 1 + 1 ) = ln 2 = e ln 2 = 2